Experimental Study on Seismic Performance of Confined Masonry Walls With Window Openings Strengthened by Using Hybrid-Fiber Modified Reactive Powder Concrete - Liu, Guo-an; Wang, Xin; Yang, Zhe; Wang, Lei-yu; Zhou, Yun-wen; Chen, Guo-bin (Frontiers in Materials, 2022)
Unreinforced masonry structures, especially for masonry structures with window openings, are very vulnerable to seismic action. Therefore, a strengthening technique needs to be proposed to improve the seismic performance of the confined masonry walls with window openings. In this study, hybrid fibers modified reactive powder concrete (HFMRPC) with good composite action to masonry walls were obtained through material tests. Then, the HFMRPC material was used as a coating to strengthen or repair the confined masonry walls with window openings by single-sided full coverage, double-sided full coverage, single-sided coverage in piers, and double-sided coverage in piers. To investigate the effectiveness of HFMRPC coating to strengthen or repair the confined masonry walls with window openings, seven half-scale masonry walls were tested under in-plane quasi-static horizontal loading. The results indicated that the retrofitting technology using HFMRPC coating can effectively enhance the load-bearing capacity, energy dissipation capacity of the strengthened and repaired masonry walls, and delay their stiffness degradation. Among the above-mentioned strengthening methods, the strengthening in piers significantly enhanced the ductility and energy dissipation of the specimens, and the double-sided full coverage enhanced the load-bearing capacity and stiffness of the specimens. Finally, a simplified analysis method to calculate the shear bearing capacity of the strengthened confined masonry walls with window openings was proposed based on theoretical analysis and test results.